2001
DOI: 10.1002/1521-4125(200103)24:3<275::aid-ceat275>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Pervaporation Separation of Benzene/Cyclohexane Mixtures by Poly(vinyl chloride) Membranes

Abstract: Sorption and pervaporation of benzene/cyclohexane mixtures were studied by using poly(vinyl chloride) (PVC) polymer. The effects of composition of benzene/cyclohexane mixture and temperature on sorption and pervaporation characteristics were determined at 30, 40, and 50 °C for the membranes containing 8 wt% PVC polymer. Liquid feed composition effects on the flux and the selectivity were determined for two different membranes at 30 °C. The membranes that were prepared from the solutions containing 4 wt% and 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…Yeang et al [14] reported a total sorption of around 0.65 g by 1 g of a blend membrane of PVA and CS filled with carbon nano tube. Yildirim et al [23] studied virgin PVC membrane for the sorption of benzene-cyclohexane mixtures. 1 g of the PVC membrane showed a total sorption of around 0.2 g of the benzene-cyclohexane mixture containing 20 wt.% benzene.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Yeang et al [14] reported a total sorption of around 0.65 g by 1 g of a blend membrane of PVA and CS filled with carbon nano tube. Yildirim et al [23] studied virgin PVC membrane for the sorption of benzene-cyclohexane mixtures. 1 g of the PVC membrane showed a total sorption of around 0.2 g of the benzene-cyclohexane mixture containing 20 wt.% benzene.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Membrane separation technology is an energy‐conservative separation process . Pervaporation (PV) is a type of membrane separation process with many applications, such as solvent dehydration and organic mixtures separation . It also has several advantages, such as easier operation and lower energy consumption, compared with conventional methods.…”
Section: Introductionmentioning
confidence: 99%
“…Benzene, which has π‐electron clouds, shows a stronger interaction with the polar or hydrophilic polymeric materials than cyclohexane. Therefore, various polar and hydrophilic membrane materials, such as polyacrylonitrile,6 polyurethanes,7 acetyl cellulose,2 poly(vinyl chloride),8 and poly(vinyl alcohol)9 were employed to separate Bz/Chx mixtures. Among them, PVA has been used as a preferred material because of its high hydrophilicity, good chemical stability, facile membrane‐forming property, and low cost.…”
Section: Introductionmentioning
confidence: 99%